Personal Development Planning of the UK Students: Implementation Models - N. Yu. Shaposhnikova (Высшее образование в России)
The aim of the article is to show the ways of the UK students’ personal development as one of the higher school answers to the challenges of the complex world of today, whose only certainty is constant change. The programme of personal development is aimed at preparing students for their future life and profession, ensuring their adaptation to the constantly changing conditions. On the basis of the analysis and comparison of the experience of three different British universities, three main implementation models of students’ personal development plans are defined. They are characterized by the type of the dominant orientation: professional, employment or academic. The professional model type was strongly influenced by the requirements of professional bodies such as health care professional bodies, and statutory bodies. The second model type, which is focused on employment, included a general orientation to graduate employment as well as specific work placement during the process of study. This model was associated with such areas as: management and business, sport and leisure, as well as those areas of applied science and engineering where the course focus was mainly towards employment rather than the discipline itself. The third – academic – model was focused on the student’s academic development. Its realization facilitated the development of metacognitive skills and the skills related to the specific subject discipline. The models presented in the article may serve as an instrument for the analysis of higher education individualization practices, and for the designing of flexible learning programmes, which take into account students’ individual abilities and learning needs.